ACCOUNTING METHODS AND PRINCIPLES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents the basics of accounting in enterprises and organizations, accounting methods and principles, scientific and theoretical views of foreign and domestic scientists on this issue, theoretical foundations of the field. The article presents conclusions and proposals for further improvement of accounting methods and principles.